Peran Ekonomi Industri dalam Mendorong Inovasi dan Pertumbuhan Ekonomi Nasional - Khairani Alawiyah; Titian Dhea Fresensia Purba; Jessica br Simanungkalit; Alexa Angelica; Kesia Septina Tarigan (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
The industrial economy plays a strategic role in driving innovation and strengthening national economic growth. As a key driver sector, industry not only contributes to the increase of Gross Domestic Product (GDP) and job creation, but also serves as a crucial platform for fostering innovation, technological transformation, and global competitiveness. This study aims to comprehensively examine the strategic role of the industrial economy in promoting innovation and national economic growth in Indonesia, while providing policy recommendations that can strengthen competitiveness in the era of Industry 4.0. The research employs a qualitative approach through a literature study, analyzing various theories, previous research findings, and secondary data from academic journals, official reports, and government documents. The analysis focuses on the interrelationship between industrial growth, innovation, competitiveness, and the contribution of the industrial sector to sustainable development. The findings reveal that the industrial sector, particularly manufacturing, contributes significantly to national GDP and creates wide-ranging multiplier effects, including employment absorption, increased household consumption, and infrastructure development. Furthermore, technological innovation through the adoption of digitalization, automation, big data, and the Internet of Things (IoT) has proven effective in enhancing productivity and product diversification. However, the sector continues to face challenges such as low global competitiveness, limited investment in research and development (R&D), dependency on imported raw materials, and sustainability issues.Therefore, this study highlights the urgency of implementing comprehensive industrial strengthening strategies through fiscal incentives, infrastructure development, intellectual property protection, and triple helix collaboration among government, industry actors, and educational institutions. The successful implementation of these strategies is expected to position Indonesia’s industrial sector as a key driver of sustainable economic growth, a national innovation hub, and a crucial pillar in achieving the vision of becoming a developed nation by 2045